2020
DOI: 10.1177/1073274820964146
|View full text |Cite
|
Sign up to set email alerts
|

Survival Rate of Colorectal Cancer in Eastern Mediterranean Region Countries: A Systematic Review and Meta-Analysis

Abstract: Colorectal cancer (CRC) is the second most common cause of cancer-related deaths worldwide. Survival rates are among the most important factors in quality control and assessment of treatment protocols. This study was aimed to assess the survival rate of colorectal cancer in Eastern Mediterranean Region Countries. In the present study we comprehensively searched 6 international databases including PubMed/Medline, ProQuest, Scopus, Embase, Web of Knowledge and Google Scholar for published articles until November… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Survival rates were studied previously (Coleman et al, 2011), with the 5-year survival rate at 16% in Ghana (Agyemang-Yeboah et al, 2018), 44% in Spain, 43.8% in Martinique (France) (Joachim et al, 2019), 63.5% in Brazil (Aguiar et al, 2020), and 66.6% in the United States (Siegel et al, 2017). This variation was observed within a region, that is, the 5-year survival rate in Eastern Mediterranean countries was 57.26% (50.43%-64.10%), which varied from 29.5% in Libya to 95% in Lebanon (Nikbakht et al, 2020). We found that the 5-year OS of Vietnamese patients with CRC was approximately 60% lower than those in Asian countries (Moghimi-Dehkordi and Safaee, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Survival rates were studied previously (Coleman et al, 2011), with the 5-year survival rate at 16% in Ghana (Agyemang-Yeboah et al, 2018), 44% in Spain, 43.8% in Martinique (France) (Joachim et al, 2019), 63.5% in Brazil (Aguiar et al, 2020), and 66.6% in the United States (Siegel et al, 2017). This variation was observed within a region, that is, the 5-year survival rate in Eastern Mediterranean countries was 57.26% (50.43%-64.10%), which varied from 29.5% in Libya to 95% in Lebanon (Nikbakht et al, 2020). We found that the 5-year OS of Vietnamese patients with CRC was approximately 60% lower than those in Asian countries (Moghimi-Dehkordi and Safaee, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…This tool has three different parts including Selection (4 questions), Comparability (1 question) and Outcome (3 questions), and based on the final scores divided into three categories: good, fair, and poor. [16][17][18][19] The global survival rate of patients with beta-thalassemia major: A systematic review and meta-analysis…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The incidence rates of CRC are the lowest in Africa and South Asia; nevertheless, the survival rate in African countries was reported to be less than 8%. 4 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…The incidence rates of CRC are the lowest in Africa and South Asia; nevertheless, the survival rate in African countries was reported to be less than 8%. 4,9 Several factors, including genetic and inflammatory bowel disease (IBD), play a significant role in the pathogenesis of CRC. Moreover, environmental factors and nutrition are closely related to the incidence and the progression of CRC.…”
Section: Introductionmentioning
confidence: 99%